“Nature, Read in Tooth and Claw”: Review of Gregersdotter et al., eds., Animal Horror Cinema: Genre, History and Criticism - Rooks, Isaac (Humanimalia, 2018)
Katarina Gregersdotter, Johan Höglund, and Nicklas Hållén, Eds. Animal Horror Cinema: Genre, History and Criticism. New York: Palgrave MacMillan, 2015. 248 pp. 95.00 hc, 69.99 e-book.